If I tell you I will have to kill you: secrecy in public administration in a time of securitization and militarization. Issue 1 (2nd January 2022) - Ericson, Mathias; Wester, Misse
ABSTRACT: Critical security studies examine how everyday life is affected or transformed by practices that militarise civil society. This article addresses one such area: qualitative changes in the openness and transparency of public administration, instating a mode of suspicion and secrecy. The article is based on interviews and observations in the area of the total defence in Sweden, where we during three years encountered challenges in gaining access to authorities that initially welcomed participation of researchers, but progressively became inaccessible. We use these experiences to reflect on both methodological issues and wider implications for the securitisation of civil society. The article concludes that difficulties in gaining access to the field may itself serve as valuable data in understanding the changing condition of public administration in a time of militarisation.